Genetics and genomics of ischemic tolerance: focus on cardiac and cerebral ischemic preconditioning. (November 2012) - Della-Morte, David; Guadagni, Fiorella; Palmirotta, Raffaele; Ferroni, Patrizia; Testa, Gianluca; Cacciatore, Francesco; Abete, Pasquale; Rengo, Franco; Perez-Pinzon, Miguel A; Sacco, Ralph L; Rundek, Tatjana
A subthreshold ischemic insult applied to an organ such as the heart and/or brain may help to reduce damage caused by subsequent ischemic episodes. This phenomenon is known as ischemic tolerance mediated by ischemic preconditioning (IPC) and represents the most powerful endogenous mechanism against ischemic injury. Various molecular pathways have been implicated in IPC, and several compounds have been proposed as activators or mediators of IPC. Recently, it has been established that the protective phenotype in response to ischemia depends on a coordinated response at the genomic, molecular, cellular and tissue levels by introducing the concept of 'genomic reprogramming' following IPC. In this article, we sought to review the genetic expression profiles found in cardiac and cerebral IPC studies, describe the differences between young and aged organs in IPC-mediated protection, and discuss the potential therapeutic application of IPC and pharmacological preconditioning based on the genomic response.